2008
DOI: 10.1111/j.1553-2712.2008.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomic Relationship of Femoral Vein to Femoral Artery in Euvolemic Pediatric Patients by Ultrasonography: Implications for Pediatric Femoral Central Venous Access

Abstract: Background: Knowledge of the femoral vein (FV) anatomy in pediatric patients is important in the selection of appropriate size central line catheters as well as the approach to central venous access. This knowledge may avoid potential complications during central line access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 8 publications
4
61
1
1
Order By: Relevance
“…Changes in leg position may reduce this overlap, but this will require immobilizing the patient in the optimal position throughout the procedure [362, 363]. …”
Section: Ultrasound-guided Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in leg position may reduce this overlap, but this will require immobilizing the patient in the optimal position throughout the procedure [362, 363]. …”
Section: Ultrasound-guided Proceduresmentioning
confidence: 99%
“…The femoral vein may be completely or partially overlapped by the femoral artery in 12 % of patients. Therefore, visualization by ultrasound is recommended prior to femoral vein catheterization [424]. …”
Section: Ultrasound-guided Proceduresmentioning
confidence: 99%
“…Ultrasound studies have shown that as many as 12% of femoral vessels in children ages 0 to 9 are either partially or completely overlapping. 13 Thus, attempts at venous access can easily result in inadvertent arterial punctures, especially if done without ultrasound guidance. The use of larger-sized arterial catheters also predisposes the child to vasospasm, resulting in potential limb ischemia.…”
Section: Anatomic and Physiologic Considerationsmentioning
confidence: 99%
“…Previous vascular studies have attempted to characterize these variables, with specific attention to the concept of overlap. [5][6][7][8] These investigations have provided limited quantitative information about the amount of overlap, however, and did not examine the amount of exposed vein. The amount of exposed femoral vein is arguably the most important factor in determining the success of central venous access.…”
Section: Ré Sumémentioning
confidence: 99%
“…Over a 12-week period, a random sampling of 180 participants who presented to the ED were enrolled. A priori sample size calculation based on previous pediatric data by Warkentine and colleagues 8 , estimated that 180 participants would be necessary to achieve 90% power.Twenty-four 4-hour blocks of time were randomly selected over the enrolment period. During these blocks, consecutive patients were approached for enrolment based on their presentation time.…”
Section: Study Design and Selection Of Participantsmentioning
confidence: 99%